2000
DOI: 10.1155/2000/732754
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Changes in Patients with Combined Chronic Schistosomiasis and Viral Hepatitis C Infections

Abstract: This study was undertaken to assess the biochemical changes induced in chronic schistosomiasis and/or chronic HCV, as well as to pinpoint the most significant parameters which could be used as dependable indices for the differentiation of single and coupled infections with or without liver cirrhosis. The selected patients were allocated into 2 broad groups: GrII (Schistosomiasis) which was subdivided into 3 subgroups: GrII(a) schistosomal patients with hepatosplenomegaly; GrII(b) hepatosplenic schistosomal pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
4
8
1
Order By: Relevance
“…An examination of the literature surrounding the use of this enzyme as a plasma marker of liver injury, however, reveals that GT is a marker for chronic persistent and progressive liver injury rather than acute liver injury. [25][26][27] Our findings support this contention.…”
Section: Discussionsupporting
confidence: 83%
“…An examination of the literature surrounding the use of this enzyme as a plasma marker of liver injury, however, reveals that GT is a marker for chronic persistent and progressive liver injury rather than acute liver injury. [25][26][27] Our findings support this contention.…”
Section: Discussionsupporting
confidence: 83%
“…This result was coordinated with Ahmed (1996) and Shalaby et al (2003a, b) and similar to Fahim et al (2000) in the case of Schistosoma patient (Manga-Gonz Lez et al 2004;Gonz Lanz et al 2006) in Dicroceolium dendiriticum but Matanovi et al (2007) recorded a decrease in AST (GOT) in sheep fascioliasis. Degenerative changes and necrosis in hepatic parenchyma were observed during histopathological examination which might be the contributory factors in their elevation.…”
Section: Discussionsupporting
confidence: 80%
“…While (Fahim et al 2000) in patients infected with Schistosoma, the albumin, total protein, and A/G ratio decreased and globulin increased.…”
Section: Discussionmentioning
confidence: 89%
“…This discrepancy of accuracy of APRI for predicting significant fibrosis could be explained by different study populations among studies. The level of albumin, the third marker in our score, falls in CHC patients as the synthetic function of the liver declines with worsening liver fibrosis since albumin is exclusively synthesized in the liver 27 . On the other hand, other studies reported slightly lower diagnostic value of albumin than our results in CHC patients with advanced liver fibrosis 28 or in CHC patients with liver cirrhosis 29 .…”
Section: Discussioncontrasting
confidence: 67%